Az energiabiztonság elmélete = The theory of energy security - Takács, Gergely (Közép-Európai Közlemények, 2018)
Following the landmark decision of Winston Churchill in 1913, oil has developed to be a strategic product even before it became a commercial item appearing on the markets. The aforementioned decision also had consequences to the course of the First and the Second World War, and affected the later efforts of the allied countries to gain influence in the Middle East. After a short historical overview of the main events of the second half of the 20th century from the perspective of the security studies, this paper wishes to present how the theories regarding energy security as a question of policy define the most crucial elements and dimensions of this field. Without presenting geopolitical and geoeconomic aspects, the theory of energy security cannot be considered as a whole, with regard to limitations of length, I would still do so. Instead, I intend to focus on theories aiming at establishing fundamental aspects, methods of calculation, indices, also with the aim of creating a new discipline.